Program Studi Tadris IPA Biologi, Universitas Islam Negeri Mataram - Rudi Ariatma; Munawir Sazali (Bioscientiae, 2026)
This study aims to identify the diversity of ferns (Pteridophyta) in the Nuraksa Forest Park (Tahura) area and analyze environmental factors that influence their distribution. The study was conducted exploratively in four locations with different habitats. Data were collected through direct observation and morphological identification using a determination key. The results showed that there were 17 species of Pteridophyta from 12 genera and 8 families. This diversity reflects the natural ecosystem conditions. Several species have economic and aesthetic value, such as Diplazium esculentum (vegetables) and Platycerium bifurcatum (ornamental plants). The identification data was used as the basis for compiling a contextual and applicable learning pocket book. This book has been proven to increase students' interest and understanding and encourage awareness of local biodiversity conservation.